Homology-based identification of candidate genes for male sterility editing in upland cotton (Gossypium hirsutum L.) - Morales, Karina Y.; Bridgeland, Aya H.; Hake, Kater D.; Udall, Joshua A.; Thomson, Michael J.; Yu, John Z. (Frontiers in Plant Science, 2022)
Upland cotton (Gossypium hirsutum L.) accounts for more than 90% of the world’s cotton production, providing natural material for the textile and oilseed industries worldwide. One strategy for improving upland cotton yields is through increased adoption of hybrids; however, emasculation of cotton flowers is incredibly time-consuming and genetic sources of cotton male sterility are limited. Here we review the known biochemical modes of plant nuclear male sterility (NMS), often known as plant genetic male sterility (GMS), and characterized them into four groups: transcriptional regulation, splicing, fatty acid transport and processing, and sugar transport and processing. We have explored protein sequence homology from 30 GMS genes of three monocots (maize, rice, and wheat) and three dicots (Arabidopsis, soybean, and tomato). We have analyzed evolutionary relationships between monocot and dicot GMS genes to describe the relative similarity and relatedness of these genes identified. Five were lowly conserved to their source species, four unique to monocots, five unique to dicots, 14 highly conserved among all species, and two in other category. Using this source, we have identified 23 potential candidate genes within the upland cotton genome for the development of new male sterile germplasm to be used in hybrid cotton breeding. Combining homology-based studies with genome editing may allow for the discovery and validation of GMS genes that previously had no diversity observed in cotton and may allow for development of a desirable male sterile mutant to be used in hybrid cotton production.